Factors associated with quality of life among menopausal women in Lucknow - A cross-sectional study - Ginic Gupta; Reema Kumari; Prabhaker Mishra; Bandna Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: Women who have gone at least a year without having their monthly period are considered as menopausal. Despite the fact that it is a physiological occurrence, its psychological, bodily, and sexual effects last for the entire postreproductive period. That's why it is important to research its various aspects and the different parameters associated with their quality of life (QoL). Objective: To find the association of the QoL among menopausal women in Lucknow with various socio-demographic variables, body mass index, chronic disease status, and other lifestyle parameters. Materials and Methods: A community-based cross-sectional study was conducted from February 2020 to January 2021 among 200 Menopausal women of 45-65 years by using a pretested semi-structured questionnaire. The study was carried out in rural and urban field practice areas of the Community Medicine Department, King George's Medical University, UP, Lucknow. Results and Conclusion: The mean score of vasomotor domains was found higher in the age group of 45-49 years, who had higher education level, upper and upper middle class of socioeconomic status, and for obese study participants. The mean score of the sexual domain was found to be higher among the age group 55-59 years, married study participants, for those who were educated above secondary, and for overweight and obese. The mean scores for all domains, i.e., vasomotor psychosocial physical and sexual domains were higher for those who had chronic diseases. Overall, the menopause specific QoL score was higher for those who did not use lifestyle modification as compared to those who used lifestyle modification and the difference was found to be highly significant (P < 0.001).